Chemoradiation of pancreatic carcinoma - Erdinç Nayır; Ekin Ermis (Journal of Oncological Sciences)
Pancreatic carcinoma is a malignancy with a poor prognosis and the 4th. most common cause of cancer-related deaths. Patients are usually diagnosed at advanced stage of the disease. Surgical resection remains the only potentially curative therapy, as only 20% of the patients present with disease are amenable to resection. Surgery, chemotherapy, radiotherapy and palliative therapies are therapeutic options. Multidisciplinary approach is needed for every stage of the disease. Researches showed an improved survival benefit of radiotherapy (RT) and chemotherapy (CT) combination for locally advanced unresectable pancreatic carcinoma compared to RT or CT alone. In an attempt to improve survival, the efficacy of chemoradiation (CRT) after surgery compared to observation has been tested in several trials. Neoadjuvant CRT achieves a higher probability of margin negative R0 resection. Currently, both 5-FU and gemcitabine have been used concurrently with RT, and also targeted agents (erlotinib, cetuximab, panitumumab, bevacizumab) have been also evaluated.